Archaean crustal evolution in West Africa: A new synthesis of the Archaean geology in Sierra Leone, Liberia, Guinea and Ivory Coast - Rollinson, Hugh (Precambrian research, 2016)
A new synthesis of the geology and geochronology of the little-known Archaean rocks in Sierra Leone, Liberia, Guinea and Ivory Coast is presented in order to better understand the processes of Archaean crustal evolution in this region, and to attempt to interpret these data in the light of our current understanding of Archaean crustal evolution. In addition, this study seeks to identify those aspects of Archaean crustal evolution which are currently not known in this area and which need to become the subject of future studies, given the economic importance of this region in terms of the mineral deposits hosted in the Archaean rocks. These include greenstone-belt hosted iron ore, lode gold, chromite and columbite–tantalite and younger diamondiferous kimberlites intrusive into Archaean felsic gneisses. The new results show that this cratonic nucleus comprises of four main geological units: (1)The oldest crust is made up of 3.5–3.6Ga TTG (tonalite–trondhjemite–granodiorite) gneisses. These only outcrop in the east of the craton in Guinea but their presence is indicated elsewhere in the central part of the craton though xenocrystic zircon cores in younger rocks.(2)The major rock type found throughout the craton is 3.26–2.85Ga TTG gneiss. In detail these magmas are thought to have formed in two episodes one between 3.05–3.26 Ga and the other between 2.85–2.96Ga. The presence of inherited zircons in the younger suite indicate that this event represents the partial reworking of the older gneisses. 3.4Ga eclogite xenoliths in kimberlite derived from the sub-continental lithospheric mantle are thought to be the restite after the partial melting of a basaltic protolith in the production of the TTG magmas.(3)Supracrustal rocks form linear belts infolded into the TTG gneisses and metamorphosed to amphibolite and granulite grade. They are of different sizes, contain a variety of lithological sequences and may be of several different ages. The larger supracrustal belts in Sierra Leone contain a thick basalt-komatiite sequence derived by the partial melting of two different mantle sources, unconformably overlain by a sedimentary formation. They are seen as an important resource for gold, iron-ore, chromite and columbite–tantalite.(4)A suite of late Archaean granitoids formed by the partial melting of the TTG gneisses in a craton wide deformation-metamorphic-partial melting event at 2800±20Ma. This thermal event is thought to be responsible for the stabilisation of the craton. This new synthesis highlights major geological and geochronological similarities between the Archaean rocks of Sierra Leone, Liberia, Guinea and Ivory Coast and those in the Reguibat Shield in the northern part of the West African Craton suggesting that the two regions were once more closely related.